Comparative Evaluation of Online and In-Class Student Team Presentations - Braun, Michael (Journal of University Teaching and Learning Practice, 2017)
Student team presentations are commonly utilised in tertiary science courses to help students develop skills in communication, teamwork and literature research, but they are subject to constraints arising from class size, available time, and limited facilities. In an alternative approach, student teams present online using a variety of tools, such as screencast and blended media, but it is not clear whether this offers an authentic alternative to in-class experience. In this study, the two modes of presentation were compared in terms of student perceptions and academic performance. A survey probed students’ familiarity with digital technology, presentation anxiety, and differential perceptions of the two modes. Aside from a confirmation bias, no significant difference was found between those who presented in class and online. In a notable exception, a clear asymmetry appeared when students were asked to choose a mode for a future presentation: none of the online presenters opted for the in-class mode while a third of in-class presenters selected the online mode. Presentation anxiety was similar for in-class and online presenters and was insensitive to gender and familiarity with English. No significant difference was detected between the modes in terms of academic performance.